REKONSTRUKSI PEMBENTUKAN AKHLAK REMAJA BERMASALAH - Murjani Murjani (EDUCATIONAL JOURNAL : General and Specific Research, 2021)
Education in the household has an important role in the formation of childhood, especially during adolescence. Therefore, education has two concepts which can form a good direction or vice versa depending on the education provided by parents to their children.